clarification

Discussion in 'Homework Help' started by jstrike21, Jan 24, 2010.

  1. jstrike21

    Thread Starter Member

    Sep 24, 2009
    104
    0
    So i know (cos(wt)+jsin(wt))= e^(jwt)
    does (cos(wt)-jsin(wt))= -e^(jwt) ?


    Also, if i have 4e^(-j*pi/6)
    does this equal 4cos(pi/6)-4jsin(pi/6)?
     
    Last edited: Jan 24, 2010
  2. t_n_k

    AAC Fanatic!

    Mar 6, 2009
    5,448
    782
    e(-jωt)=cos(ωt)-jsin(ωt)

    -e(jωt)=-cos(ωt)-jsin(ωt)
     
  3. jstrike21

    Thread Starter Member

    Sep 24, 2009
    104
    0
    1. Simplify
    [cos(w t) + j sin(wt)] * [cos(2 w t) - j sin(2 w t)]
    and leave the result in polar form.

    =(e^(jwt))*(e^(-2jwt))
    =e^(-jwt)
    correct?
     
Loading...